ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PEKERJA DI KABUPATEN/KOTA PROVINSI BALI - Jayananda, I Wayan Ega; Marhaeni, A. A. I. N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p13, 2023)
This study aims to analyze the effect of education level, health status, wage level, and use of information and communication technology (ICT) either simultaneously or partially on worker productivity in the regency/city of Bali Province, as well as to determine the role of ICT use in moderating the effect of education level on worker productivity in the regency/city of Bali Province. This study uses panel data, namely a combination of time series data and cross section with a total of 63 observation points. The data collection method is done through observation with secondary data. The data analysis technique used in this study is a moderation regression analysis. The results of this study indicate that the education level, health status, wage level, and use of ICT have a significant effect on worker productivity in regency/city of Bali Province. Partially, the health status has a positive and significant effect on worker productivity in the regency/city of Bali Province, while the variables of education level, wage level, and use of ICT have no significant effect on worker productivity in the regency/city of Bali Province. The use of ICT is not able to moderate the effect of education level on worker productivity in regency/city of Bali Province